(untitled) (Research, Society and Development, 2022)
Objective: To describe the experience of students participating in an extension project in the creation and use of digital technology, as a playful tool for the continuity of storytelling activities to hospitalized children during the COVID-19 pandemic. Method: This is a descriptive study, of an experience report type, which took place at a Public University, located in the central-west region of Minas Gerais, through the Contos Project: the art of humanizing the pediatric environment in health institutions, developed by undergraduate and graduate students in Nursing and Computer Sciences. Results: The experience from March 2020 to March 2021, demonstrated that after the interruption of on-site extension activities, there is the possibility of continuing extension actions using digital technology, giving an opportunity for playful care to children. hospitalized child, and the articulation of teaching, research and extension for students who experience education in the virtual modality. Final Considerations: The creation and use of digital technology is an important tool for access to children and families who experience hospitalization in this time of pandemic. In addition to promoting the articulation of extension with health institutions, providing a new way of learning to extension students.